Effectiveness of nonsurgical periodontal therapy on the levels of Helicobacter pylori in dental plaque and saliva of patients with chronic periodontitis - Venkata, Tejaswini; Chickanna, Rudrakshi; Prabhuji, M. L. V. (European Journal of General Dentistry, 2017)
Objectives: Presence of Helicobacter pylori in the oral cavity may enhance the risk for gastric re-infection; hence, the present study was carried out to detect and compare the levels of H. pylori in subgingival plaque and saliva of patients with periodontal health and chronic periodontitis at baseline and 3 months following scaling and root planing (SRP). Methods: A total of 45 patients with 30 patients having chronic periodontitis (test group) and 15 periodontally healthy patients (control group) were considered. H. pylori was detected in subgingival plaque and saliva samples, collected at baseline and at 3 months using polymerase chain reaction. Clinical parameters were recorded at baseline, 1 month, 2 months, and 3 months. Results: At the baseline, in test group 60% and 40% of the samples were positive for H. pylori and in control group 26.7% and 13.3% of the samples were positive for H. pylori in subgingival plaque and saliva, respectively. At 3 months, 26.7% and 20% samples were positive for H. pylori in the test group and in control group 13.3% and 6.7% samples were positive for H. pylori in subgingival plaque and saliva, respectively, demonstrating higher levels of H. pylori in dental plaque than in saliva. There was a significant reduction in the percentage of H. pylori in subgingival plaque following SRP. Conclusion: Periodontal treatment has shown to be effective in reducing the levels of H. pylori from the oral cavity.
Keywords: Chronic periodontitis; dental plaque; scaling and root planing